Pinhole does not increase screening accuracy of detecting decreased best corrected visual acuity in schoolchildren - Weiwei Chen (BMC, 2021)
Abstract Background Decreased best corrected visual acuity among children should be treated early in life, and vision screening in schoolchildren is an efficient and feasible selection for developing countries. Thus, the screening accuracy of different visual acuity tests is the key point for making vision screening strategies. The present study aims to explore the screening accuracy of uncorrected visual acuity (UCVA) and pin-hole corrected visual acuity (PCVA) using different vision chart in the detection of decreased best-corrected visual acuity (BCVA) among schoolchildren. Methods Grade one primary schoolchildren in urban Lhasa with data of UCVA using tumbling E chart (UCVAE), PCVA using tumbling E chart (PCVAE), UCVA using Lea Symbols chart (UCVAL), PCVA using Lea Symbols chart (PCVAL) and BCVA using Lea Symbols chart were reviewed. Decreased BCVA was defined as BCVA≤20/32(≥0.2 logMAR). Difference, reliability, and diagnostic parameters in the detection of decreased BCVA of different visual acuity results were analyzed. Results Overall, 1672 children aged 6.58 ± 0.44 years fulfilling the criteria. The prevalence of decreased BCVA was 6.8%. Although no significant differences were found between UCVAE vs UCVAL (p = .84, paired t-test) as well as PCVAE vs PCVAL (p = .24), the ICC between them was low (0.68 and 0.57, respectively). The average difference between BCVA and UCVAE, UCVAL, PCVAE, PCVAL was logMAR -0.08 (− 0.37, 0.21), − 0.08 (− 0.29, 0.17), − 0.05 (− 0.30, 0.19), − 0.06 (− 0.23, 0.12) using Bland–Altman method. The area under the receiver operating characteristic curve of UCVAE, PCVAE, UCVAL, PCVAL for the detection of decreased BCVA was 0.78 (0.73, 0.84), 0.76 (0.71, 0.82), 0.95 (0.94, 0.96), 0.93 (0.91, 0.95), respectively. Conclusion Pinhole does not increase the screening accuracy of detecting decreased BCVA in grade one primary schoolchildren. Visual acuity test using Lea Symbols is more efficient than Tumbling E in the screening of that age. Trial registration Data were maily from the Lhasa Childhood Eye Study which has finished the clinical registration on ( ChiCTR1900026693 ).